Dynamic Performance Investigation of Solar‐Driven Vapor Absorption Cooling System for Urban Areas - Laveet Kumar; Hamza Shaikh; Ahmad K. Sleiti; Muhammad Amir Raza (Engineering Reports)
ABSTRACT Solar energy in urban areas due to excessive air conditioning usage in buildings may significantly reduce the consumption of fossil fuels. This study uses TRNSYS to undertake the thermal performance analysis of solar‐driven vapor absorption cooling systems for several urban cities in Pakistan with varying climatic conditions. Two separate solar collectors—flat plate collector (FPC) and evacuated tube collector (ETC)—are used to simulate the cooling system. The system's performance is evaluated based on the solar fraction (SF) and primary energy savings. The results of simulation showed that ETC would be a better choice regarding the selection of solar collector as the system with ETC achieved a higher SF and primary energy saving (fsaving,shc). The SF ranges from 13% to 78% and 13% to 64% for ETC and FPC, respectively. The primary energy saving ranges from 75% to 93% and 75% to 96% with flat plate and ETC, respectively. For both flat plate and ETCs, increasing the collector area increased the SF and primary energy savings while increasing the capacity of thermal storage decreased the SF and primary energy savings. For varying thermal storage volumes, the SF varies very little when using flat plate collector but significantly when using ETC. The best thermal performance was recorded in Peshawar based on the SFs and primary energy saving.